Pastoralism in Algeria: transformation, challenges and prospects - Moussaoui A.; Abbas K.; Bottalico F.; Ottomano Palmisano G.; El Bilali H. (Pastoralism and sustainable development: proceedings, 2021)
Pastoralism plays a significant socio-economic role in Algeria. However, extensive livestock systems, which are of high nature value, are facing many challenges and their decline might have social, economic and environmental consequences. In this context, the present review contributes to a better understanding of the current situation in which pastoralism in Algeria is evolving and the major developments over the last decades. It draws upon secondary data from the scholarly literature as well as grey one (e.g. reports). The analyzed literature suggests that the pastoral regions in Algeria are subject to a number of social, economic and technical transformations. These transformations occur as a result of the breakdown of traditional balances between social groups and natural resources. The socioeconomic factors induced by demographic growth as well as climate change have also profoundly modified the Algerian pastoral systems (cf. decreased mobility, greater dependence on feed supplements). This study reveals livestock systems and practices instability as well as an increase of competition over pastoral resources use. The results also highlight that in the face of those transformations, pastoral societies are becoming economically fragile, pushing pastoralists towards livelihoods diversification to improve their chances of maintaining their farms in economically and climatically difficult conditions.
International e-Workshop organized in the framework of PACTORES project, 2021/07/14-15, Valenzano, Bari, (Italy)